CHANGES TO THE NATURAL GAS, CORN, AND FERTILIZER PRICE RELATIONSHIPS FROM THE BIOFUELS ERA. (11th November 2015) - BECKMAN, JAYSON; RICHE, STEPHANIE
Abstract: The biofuels era brought about changes to the energy and agricultural sectors. For example, the decrease in natural gas prices has led to a weakening of the relationship between fertilizer and gas prices. The other change has been an increase in the demand for fertilizers, which has strengthened the price relationship between these two products. Econometric evidence from this work indicates that after 2008 the relationship between fertilizers and corn prices increased. In addition, results from our work indicate the presence of market power in the ammonia fertilizer sector.